Distinctive downmodulation of plasmacytoid dendritic cell functions by vitamin D3 analogue calcipotriol. Issue 1 (October 2016) - Suzuki, Takahiro; Tatsuno, Kazuki; Ito, Taisuke; Sakabe, Jun-ichi; Funakoshi, Atsuko; Tokura, Yoshiki
Highlights: Calcipotriol (CAL) exerts immunomodulating effects on murine plasmacytoid dendritic cells (pDCs). CAL inhibited IFN-α production from pDCs. CAL depressed chemotactic activities of pDCs toward chemokines. CAL may improve psoriasis by inhibiting pDCs. Abstract: Background: In relation to Th17 cell actions, interferon (IFN)-α production by plasmacytoid dendritic cells (pDCs) are involved in the pathogenesis of psoriasis. Vitamin D3 analogues are widely used in the treatment of psoriasis, however, their actions on pDCs are not well understood. Objective: To investigate the effects of Vitamin D3 analogue calcipotriol (CAL) on pDCs, focusing on the cytokine production and chemotactic activity. Methods: We compared in mice the effects of CAL, cyclosporine A (CyA), and triamcinolone acetonide (TA) on the cytokine production by pDCs (IFN-α), conventional DCs (TNF-α), and γd T cells (IL-17A). pDCs isolated from mouse spleen cells were stimulated with CpG-ODN in the presence or absence of each drug for 48 h. Purified splenic conventional DCs (cDCs) and lymph node γδ T cells were stimulated with CpG-ODN or with anti-CD3/CD28 antibody, respectively. IFN-α, TNF-α and IL-17A in the 48-h culture supernatants were quantified by ELISA. We also studied the ability of CAL to inhibit the chemotaxis of freshly isolated pDCs toward chemerin and VEGF-A, representative chemoattractants of pDCs, by a real-time monitoring method, EZ-Taxiscan. To assess the effect of CAL on pDC accumulation in vivo, we painted CAL ointment to the mouse skin inflamed by topical application of imiquimod cream (IMQ) for 4 consecutive days. In the skin samples, we enumerated 440c + pDCs by immunohistochemistry and evaluated the mRNA expression of cytokines by real-time PCR. Results: CAL significantly inhibited CpG-enhanced pDC IFN-α production at a comparable level to T cell IL-17A production, whereas its effect on cDC TNF-α production was minimal. Accordingly, CAL suppressed the CpG-augmented expression of TLR9 and MyD88. On the contrary, CyA strongly suppressed the production of TNF-α and IL-17A, but not IFN-α. TA inhibited the production of all the cytokines tested. The effect of CAL on the chemotactic activity of pDCs was also evaluated, demonstrating a significant downmodulation by exposure to the reagent. CAL depressed chemerin receptor CMKLR1 expression in pDCs. The in vivo mouse study showed that simultaneous application of CAL to the imiquimod-applied skin reduce both the recruitment of pDCs and the expression of IFN-α2 in the skin. Conclusions: Our findings suggest that CAL uniquely downmodulates the cytokine production and chemotactic activity of pDCs. The CAL suppression of the in vivo pDC accumulation to the skin suggests that these actions are therapeutically relevant.